Research Progress on the Role and Mechanism of Action of Activin A in Brain Injury - Su, Xiaojuan; Huang, Lingyi; Xiao, Dongqiong; Qu, Yi; Mu, Dezhi (Frontiers in Neuroscience, 2018)
Activin A belongs to the transforming growth factor superfamily and has a variety of biological functions. Studies have revealed that activin A can regulate the body's immune and inflammatory responses and participate in the regulation of cell death. In addition, activin A also has neurotrophic function and plays an important role in the repair of brain damage. This article summarizes recent advances in understanding the role and mechanism of action of activin A in brain injury and provides new hints into the application of activin A in the treatment of brain injury.